The Common between Malay Language and the Qur'an A model of curriculum for teaching Arabic to Malay speakers - Mahmoud Thabet Ibrahim (UIN Fatmawati Sukarno Bengkulu, 2022)
AbstractThe Arabic language has a high position in the hearts of Muslims and their conscience, and there is no surprise in that; as it is the language of the holy Quran and the language of the noble hadith that the Noble Prophet uttered, and it is also the language of the honourable people of Paradise, and it is no wonder, then, that Muslims like learning the Arabic language. Study Problem: It is known that teaching Arabic to native speakers is different from the way it is taught to native speakers. It is also known that learning Arabic for Muslims is very important to master the recitation of the Holy Qur'an, and understand its secrets; so this study came to try to walk the way to teach Arabic and teach the Qur'an at the same time.